Increased Activities against Biofilms of the Pathogenic Yeast Candida albicans of Optimized Pom-1 Derivatives - Valerie Amann; Ann-Kathrin Kissmann; Markus Krämer; Imke Krebs; Julio A. Perez-Erviti; Anselmo J. Otero-Gonzalez; Fidel Morales-Vicente; Armando Rodríguez; Ludger Ständker; Tanja Weil; Frank Rosenau (Pharmaceutics, 2022)
Antimicrobial peptides (AMPs) are an alternative group for the therapy of infectious diseases, with activity against a wide range of diverse pathogens. However, classical AMPs have significant side effects in human cells due to their unspecific pore formation in biomembranes. Nevertheless, AMPs are promising therapeutics and can be isolated from natural sources, which include sea and freshwater molluscs. The AMPs identified in these organisms show promising antimicrobial activities, as pathogens are mainly fought by innate defence mechanisms. An auspicious candidate among molluscs is the Cuban freshwater snail Pomacea poeyana, from which the peptides Pom-1 and Pom-2 have been isolated and studied. These studies revealed significant antimicrobial activities for both AMPs. Based on the activities determined, Pom-1 was used for further optimization. In order to meet the emerging requirements of improved anti-biofilm activity against naturally occurring Candida species, the six derivatives Pom-1A to F were developed and investigated. Analysis of the derivatives acting on the most abundant naturally occurring Candida yeast Candida albicans (C. albicans) revealed a strong anti-biofilm activity, especially induced by Pom-1 B, C, and D. Furthermore, a moderate decrease in the metabolic activity of planktonic yeast cells was observed.